AS CULTURAS JUVENIS: UM DIÁLOGO POR MEIO DA CULTURA CORPORAL DE MOVIMENTO - Lucas Silvestre dos Santos; Márcia Regina Canhoto de Lima; José Milton de Lima; Kelly da Silva Oliveira; Rodrigo Menegon (Universidade do Oeste Paulista, 2014)
The youths and its manifestations has gained more and more space in academia, that motivated his interest in research. Based on the Sociology of youth we seek to know and understand the manifestations of youth cultures, present in a room of high school to a public school in the city of Presidente Prudente. How they relate to one another and through the discipline of physical education-based on the principles of body Culture Movement-you can create a channel of dialogue between the same and consequently with the school. We use the methodology of the ethnographic type in this, the researcher is part of the analysis medium, aiming to meet the daily life of social actors. Thus, we observe the dynamism present in the school context, such as its heterogeneity. It was also noticeable that, through the discipline of physical education, it was possible to create a Dialogic channel, being class a space for cultural exchange and collective buildings, an eminently juvenile environment.